Chemical composition of the essential oil of the Mangabeira (Hancornia speciosa Gomes) fruit from Tocantins (Research, Society and Development, 2022)
Mangaba is a fruit of the mangabeira (Hancornia speciosa Gomes), a originated from the Brazilian cerrado, with alimentary and medicinal potential. The aim of this work was to analyses the chemical composition of aroma essential oil of mangaba fruit from the regions of Lajeado and Filadélfia of the state Tocantins. Analyses were performed at the Chromatography Laboratory (LABCROM-UFT) of the Federal University of Tocantins Campus Araguaína-Cimba. To get the chemical profiles two methods of extraction were carried out (hydrodestillation and liquid-liquid), separation and identification of the volatile compounds of essential oil were by gas chromatography coupled to mass spectrometry (GC-MS). The results of the chemical profile of mangaba essential oil showed the presence of esters (methyl salicylate, ethyl benzoate), alcohols (linalool, phenylethyl alcohol, citronellol, geraniol, eugenol, benzyl alcohol), carboxylic acids (benzene propanoic acid, 2,4-dimethyl-pentanoic acid), hydrocarbons (decane, 2,5 cyclohexadiene), aldehydes (undecanal, dodecanal, benzene acelaldehyde), ketones (acetophenone). Alcohols being the abundant specific compounds in essential oil. The research showed the potential of this fruit in the food, pharmaceutical and cosmetic industry, as well as the sustainable explotation and biological preservation of the mangabeira and its fruit.